Karakterisasi Bakteri Asam Laktat dan Total Asam Organik Ekoenzim Asal Filtrat Feses Sapi Potong dan Jerami Padi Pada Lama Fermentasi yang Berbeda - Sari, Aisa Hafidah; Marlina, Eulis Tanti; Hidayati, Yuli Astuti (Unpad Press, 2024)
The objective of the research is to identify the effect of fermentation time on ecoenzymes from a mixture of beef cattle feces and rice straw on amount of lactic acid bacteria and total organic acids. The filtrate was from a mixture of beef cattle feces and rice straw with a C/N of 30 and decomposed for 7 days. The filtrate is mixed with molasses and water, fermented by facultative anaerobes. The research method used a Completely Randomized Design (CRD) with 4 treatments fermentation duration, P1=7 days, P2=14 days, P3=21 days, P4=28 days, with 5 repetitions. The parameters measured are amount of lactic acid bacteria, total organic acids, and macroscopic and microscopic characterization of lactic acid bacteria. Data were analyzed using the Analysis of Variance (ANOVA) method with Tukey's advanced test. The number of lactic acid bacteria and total organic acids with the highest value was obtained at a fermentation time of 7 days. Macroscopic characterization of lactic acid bacteria is white and cream in color, round shape, convex elevation, smooth edges and shiny surface, with microscopic characteristics is gram-positive bacteria with a bacil shape.